Learning difficulties among primary pupils: A case study in KNUST primary, Kumasi. - Narh, Sylvester Kofi (2017)
A Thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Philosophy in Art Education Faculty of Art, College of Art and Built Environment, Department of General Arts Studies, .